Wild religion : tracking the sacred in South Africa - Chidester, David (Binghamton University Music Department tape recordings ;, 2012)
Wild Religion is a wild ride through recent South African history from the advent of democracy in 1994 to the euphoria of the football World Cup in 2010. In the context of South Africa's political journey and religious diversity, David Chidester explores African Indigenous religious heritage with a difference. As the spiritual dimension of an African Renaissance, Indigenous religion has been recovered in South Africa as a national resource. Wild Religion analyses Indigenous rituals of purification on Robben Island, rituals of healing and reconciliation at the new national shrine, Freedom Park.